Wage inequality and informality: Evidence from Mexico - Chiara Binelli (IZA Journal of Labor & Development, 2016)
While several studies have documented the expansion of the informal sector and its detrimental impact on development, few have noted that informality and wage inequality tend to move together. Using Mexico as a case study, I show that between 1987 and 2002 wage inequality within informal workers accounted for over 60% of total wage inequality and that the Mexican financial crisis of the mid-1990s increased the share of informal workers and, via this, wage inequality. The results provide supportive evidence that in Mexico higher wage dispersion is one of the channels through which informality negatively affects development.
Keywords: O17; J31; C36; 330; Wage inequality; Informality; Mexico